Compendium for Early Career Researchers in Mathematics Education - Kaiser, Gabriele; Presmeg, Norma; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The purpose of this Open Access compendium, written by experienced researchers in mathematics education, is to serve as a resource for early career researchers in furthering their knowledge of the state of the field and disseminating their research through publishing. To accomplish this, the book is split into four sections: Empirical Methods, Important Mathematics Education Themes, Academic Writing and Academic Publishing, and a section Looking Ahead. The chapters are based on workshops that were presented in the Early Career Researcher Day at the 13th International Congress on Mathematical Education (ICME-13). The combination of presentations on methodological approaches and theoretical perspectives shaping the field in mathematics education research, as well as the strong emphasis on academic writing and publishing, offered strong insight into the theoretical and empirical bases of research in mathematics education for early career researchers in this field. Based on these presentations, the book provides a state-of-the-art overview of important theories from mathematics education and the broad variety of empirical approaches currently widely used in mathematics education research. This compendium supports early career researchers in selecting adequate theoretical approaches and adopting the most appropriate methodological approaches for their own research. Furthermore, it helps early career researchers in mathematics education to avoid common pitfalls and problems while writing up their research and it provides them with an overview of the most important journals for research in mathematics education, helping them to select the right venue for publishing and disseminating their work.
Section I: Empirical methods -- 1 Argumentation analyses for early career researchers. Christine Knipping and David Reid 10500 -- 2 Topic-specific design research: An introduction. Koeno Gravemeijer, Susanne Prediger 9990 -- 3 A naturalistic paradigm: An introduction to using ethnographic methods for research in mathematics education. Judit Moschkovich 9150 -- 4 An introduction to grounded theory with a special focus on axial coding and the coding paradigm. Maike Vollstedt and Sebastian Rezat 8900 -- 5 Interactional analysis: A method for analyzing mathematical learning processes in interaction. Marcus Schuette, Rachel-Ann Friesen, and Judith Jung 12750 -- 6 Planning and conducting mixed methods studies in mathematics education research. Nils Buchholtz 9750 -- 7 The research pentagon: A tool with which to think about research. Angelika Bikner 8700 -- 8 Qualitative text analysis: A systematic approach. Udo Kuckartz 6350 -- 9 The ontological grounding of three research projects in mathematics education employing video: Problematising video as data. Esther Chan, Carmel Mesiti, and David Clarke 7650 -- Section II: Important mathematics educational themes -- 10 Approaching proof in the classroom through the logic of inquiry. Ferdinando Arzarello and Carlotta Soldano 10200 -- 11 A friendly introduction to "Knowledge in Pieces": Modeling types of knowledge and their roles in learning. Andrea diSessa 9300 -- 12 Task design frameworks in mathematics education research: An example of a domain-specific frame for algebraic learning with technological tools. Carolyn Kieran 10800 -- 13 Gender and mathematics education: An overview. Gilah Leder 8700 -- 14 Theoretical aspects of mathematics education: Doing research in mathematics education: An argument for coherence. Stephen Lerman 7700 -- 15 The professional development of teachers of mathematics. Björn Schwarz and Gabriele Kaiser 7500 -- Section III: Academic writing and academic publishing -- IIIa Academic writing -- 16 Pleasure, power, and pitfalls of writing up mathematics education research. Norma Presmeg and Jeremy Kilpatrick 5200 -- 17 Scholarly writing. Helen Forgasz 5500 -- IIIb Description of major journals in mathematics education -- 18 Educational Studies in Mathematics (Merrilyn Goos) 5900 -- 19 For the Learning of Mathematics (David Reid and Richard Barwell) 5800 -- 20 International Journal of Science and Mathematics Education (Peter Liljedahl) 6300 + 2000 -- 21 Journal for Research in Mathematics Education (Jinfa Cai, Stephen Hwang, and Victoria Robison) 7200 -- 22 Journal of Mathematical Behavior (Carolyn Maher) 2900 -- 23 Journal of Mathematics Teacher Education (Despina Potari) 4900 -- 24 Mathematical Thinking and Learning (Lyn English) 5600 -- 25 ZDM Mathematics Education (Gabriele Kaiser) 6000 -- Section IV: Looking ahead -- 26 What makes for powerful classrooms, and how can we support teachers in creating them? A story of research and practice, productively intertwined: Alan Schoenfeld 6100 -- 27 If we want to get ahead, we should transcend dualisms and foster paradigm pluralism. Thorsten Scheiner 9500.
Keywords: 9; Education-Research.; Study skills; Mathematics Education; Research Methods in Education; Writing Skills; Research Skills